2018
DOI: 10.1002/fsn3.621
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and aflatoxin contents of traditional complementary foods consumed by children of 6–24 months

Abstract: The nutrient composition and safety of complementary foods have recently become areas of concern, especially with regard to aflatoxin contamination which has been found to adversely affect health outcomes. This study presents the nutrient and aflatoxin contents of complementary foods consumed by children (6–24 months) and infants and young child feeding practices of mothers from two districts in eastern and southern Zambia. A total of 400 mother–child pairs were recruited from Monze and Chipata districts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…However, the children from Monze had a higher value of AFB1-lys and AFB1-lys normalised to albumin measured, which suggests higher exposure. Alamu et al (2018) showed that the complementary foods the children were fed on during the sampling period contained aflatoxins at levels (Porridge-mean 5.8 ± 15.93 mg/kg) and Nshima-mean 3.8 ± 6.41 mg/kg) that were at times exceeding the recommended maximum tolerable limit (2.0 mg/kg) in baby foods. Thus, exposure to aflatoxin through consumption of contaminated complementary foods coupled with ingestion of aflatoxin M1 in the breast milk of exposed mothers may have contributed to the levels detected in the serum in the present study.…”
Section: Serum Aflatoxin Concentrations Of Children Of 6-24 Monthsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the children from Monze had a higher value of AFB1-lys and AFB1-lys normalised to albumin measured, which suggests higher exposure. Alamu et al (2018) showed that the complementary foods the children were fed on during the sampling period contained aflatoxins at levels (Porridge-mean 5.8 ± 15.93 mg/kg) and Nshima-mean 3.8 ± 6.41 mg/kg) that were at times exceeding the recommended maximum tolerable limit (2.0 mg/kg) in baby foods. Thus, exposure to aflatoxin through consumption of contaminated complementary foods coupled with ingestion of aflatoxin M1 in the breast milk of exposed mothers may have contributed to the levels detected in the serum in the present study.…”
Section: Serum Aflatoxin Concentrations Of Children Of 6-24 Monthsmentioning
confidence: 99%
“…The introduction of complementary foods may expose children to diseases and infections from unsafe food (which may include aflatoxins), water contamination, and poor hygiene. Maize and groundnut form the basis of complementary foods owing to their high production levels (Alamu et al 2018). These are common for children in poor households and are given in the form of maize porridge with groundnut added to enhance protein and energy density cheaply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other settings, focus group discussions among caregivers who were mixing maize with legume flours for more nutrient-dense porridges revealed the use of shrivelled, discolored, and damaged groundnuts in those complementary foods (Geresomo et al 2017). Research from neighboring Zambia found that traditional maize-based complementary foods similar to Malawian nsima and mixed-flour porridge did not meet recommended nutrient levels for CFs and were contaminated with higher than recommended levels of aflatoxin (Alamu et al 2018). As in other low-income settings (Choudhury, Headey, and Masters 2019), very few households use high-cost foods such as eggs, meat or even fruits and vegetables, and most preparedat-home porridges use local starchy staples, sometimes combined with local leguminous grains.…”
Section: Child Malnutrition and Feeding Practices In Malawimentioning
confidence: 99%
“…La presencia de micotoxinas en alimentos comerciales para lactantes ha sido reportada alrededor del mundo de manera creciente y sostenida, sobre todo en países en vías de (12)(13)(14) desarrollo . En consecuencia, se han establecido normativas sobre los límites máximos de estos contaminantes.…”
Section: Introductionunclassified